Why Aging T Cells Fail: Implications for Vaccination - Haynes, Laura (Immunity, 2006)
The decline in CD4(+) T cell function with aging contributes to reduced vaccine efficacy. In this commentary, we discuss the factors leading to age-related changes in T cell function and propose how they may be overcome to enhance vaccine efficacy for the elderly.